Toxicological investigation in blood samples from suspected impaired driving cases in the Milan area: Possible loss of evidence due to late blood sampling. (July 2018) - Ferrari, Davide; Manca, Monica; Premaschi, Simone; Banfi, Giuseppe; Locatelli, Massimo
Highlights: The time gap between crash and blood collection must be taken into account for a correct DUID evaluation. Smoked THC clearance is rapid and often leading to wrong DUID evaluation. The 2 and 10 ng/ml cut-off limits for THC and cocaine respectively might be inappropriate. A corrective time-factor might contribute to a more fair evaluation of DUID. The 0.5 mg/ml cut-off limits for alcohol blood concentration is appropriate. Abstract: Driving under the influence of illicit drugs (DUID) represents a significant menace to public safety and is therefore sanctioned with severe fines and penalties such as driving disqualification or even arrest in case the accident has caused serious injury or death. In Italy, DUID is regulated by the article 187 of the National Street Code, however, the list of the substances to be searched and their threshold concentrations are left to the 20 Italian regional authorities. A further lack of legislative standardization concerns the type of detection methods and moreover the time gap between the car accident and blood sampling. This interval can be as high as 5 h, enough to significantly reduce the concentration of drugs with fast pharmacokinetic. By analyzing 1258 blood tests performed on drivers involved in road traffic crashes in the Milan area between 2012 and 2016 we show that approximately 75% of such drivers who tested positive for THC and 15% of the drivers who tested positive for cocaine are at risk of misjudgment. Considering the severe sanctions associated with DUID, we emphasize the urgency of introducing a corrective factor that takes into account the time elapsed between the accident and blood sampling in order to avoid unfair treatment, including the unjust application of sanctions.